2009
DOI: 10.1002/app.29866
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of poly(D,L‐lactic acid)‐b‐poly(ethylene glycol)‐b‐poly(D,L‐lactic acid) copolymer by electron beam radiation

Abstract: This article investigates the effects of electron beam (EB) radiation on poly(D,L-lactic acid)-b-poly (ethylene glycol) copolymer (PLA-b-PEG-b-PLA). The copolymer films were EB irradiated at doses from 0 to 100 kGy. The degradation of these films was studied by measuring the changes in their molecular weight, mechanical and thermal properties. The dominant effect of EB radiation on PLA-b-PEG-b-PLA is chain-scission. With increasing irradiation dose, recombination reactions or partial crosslinking may occur in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Baick et al reported the reversible oligomerization of L-lactic acid in this binary catalyst system [24]. Miao et al applied this binary catalyst method to the synthesis of PLA-PEG-PLA triblock copolymers [25]. The reaction time, temperature, pressure and ratio of binary catalysts were studied to determine their effect on polymer decomposition, discoloring and racemization [14][15][16]24,25].…”
Section: Racemizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Baick et al reported the reversible oligomerization of L-lactic acid in this binary catalyst system [24]. Miao et al applied this binary catalyst method to the synthesis of PLA-PEG-PLA triblock copolymers [25]. The reaction time, temperature, pressure and ratio of binary catalysts were studied to determine their effect on polymer decomposition, discoloring and racemization [14][15][16]24,25].…”
Section: Racemizationmentioning
confidence: 99%
“…Miao et al applied this binary catalyst method to the synthesis of PLA-PEG-PLA triblock copolymers [25]. The reaction time, temperature, pressure and ratio of binary catalysts were studied to determine their effect on polymer decomposition, discoloring and racemization [14][15][16]24,25]. We previously reported that a reaction time longer than 20 h in melt polycondensation of PLLA was ineffective for further polymerization, but rather induced discoloration and racemization of PLLA [14].…”
Section: Racemizationmentioning
confidence: 99%
“…Although some data on the effects of electron-beam (EB) irradiation on PLA and its copolymers have been published [38,39,40], no studies have been reported so far regarding the effects of radiation on the properties of PLA- co -PTMC copolymers. In the present work, chemical changes occurring upon irradiation of diblock and random copolymers of various molar compositions were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, electron beam (e-beam) radiation has been shown to modify the physical properties of PLGA and PLLA and their copolymers, 26 upon which tunable hydrolysis rates from these polymers can be achieved. 27,28 Preliminary drug release results from these irradiated polymer films also show that radiation accelerates the onset (or reduces the lag phase) of drug release from these bulk degrading polymers (results not published).…”
Section: Introductionmentioning
confidence: 99%